Association of Lipid Levels With COVID-19 Infection, Disease Severity and Mortality: A Systematic Review and Meta-Analysis - Chidambaram, Vignesh; Shanmugavel Geetha, Harinivaas; Kumar, Amudha; Majella, Marie Gilbert; Sivakumar, Ranjith Kumar; Voruganti, Dinesh; Mehta, Jawahar L.; Karakousis, Petros C. (Frontiers in Cardiovascular Medicine, 2022)
Background Coronavirus disease 2019 (COVID-19) ranges from asymptomatic infection to severe illness. Cholesterol in the host cell plasma membrane plays an important role in the SARS-CoV-2 virus entry into cells. Serum lipids, especially low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C), are in constant interaction with the lipid rafts in the host cell membranes and can modify the interaction of virus with host cells and the resultant disease severity. Recent studies on serum lipid levels and COVID-19 disease severity lack consistency. Objectives Our systematic review and meta-analysis compared the serum levels of total cholesterol (TC), LDL-C, HDL-C, and triglycerides (TG) between 1) COVID-19 patients vs. healthy controls; 2) severe vs. non-severe COVID-19 disease; 3) deceased vs. surviving COVID-19 patients. Methods PRISMA guidelines were followed. We included peer-reviewed articles on observational (case-control and cohort) studies from PubMed and Embase published from the database inception until September 1, 2021. We used random-effects meta-analysis for pooled mean-differences (pMD) in lipid levels (mg/dL) for the above groups. Results Among 441 articles identified, 29 articles (26 retrospective and 3 prospective cohorts), with an aggregate of 256,721 participants, were included. COVID-19 patients had lower TC (pMD-14.9, 95%CI-21.6 to -8.3) and HDL-C (pMD-6.9, 95%CI -10.2 to -3.7) levels (mg/dL). Severe COVID-19 patients had lower TC (pMD-10.4, 95%CI -18.7 to -2.2), LDL-C (pMD-4.4, 95%CI –8.4 to -0.42), and HDL-C (pMD-4.4, 95%CI –6.9 to -1.8) at admission compared to patients with non-severe disease. Deceased patients had lower TC (pMD-14.9, 95%CI -21.6 to -8.3), LDL-C (pMD-10.6, 95%CI -16.5 to -4.6) and HDL-C (pMD-2.5, 95%CI -3.9 to -1.0) at admission. TG levels did not differ based on COVID-19 severity or mortality. No publication bias was noted. Conclusions We demonstrated lower lipid levels in patients with COVID-19 infection and an association with disease severity and mortality. Their potential role in COVID-19 pathogenesis and their utility as prognostic factors require further investigation.